Analisis Strategi Komunikasi Pemasaran untuk Meningkatkan Brand Awareness terhadap PT. Morige Nusa Tenggara Timur - Rotok, Alfianah; Salean, Debryana Y.; Wijayanti, Nadia S.; Bunga, Markus (Lembaga Yasin AlSys, 2025)
This study aims to analyze the marketing communication strategies implemented by PT. Morige Nusa Tenggara to enhance brand awareness as a local food processing enterprise specializing in moringa and sorghum-based products. The core issue explored in this research is the relatively low level of brand awareness in the local market, even though the company’s products have gained recognition at both national and international levels. This paradox highlights the importance of localized and culturally relevant marketing efforts. To address this challenge, the company adopts a variety of marketing communication strategies designed to reach and engage consumers more effectively. The study uses a descriptive qualitative method, with data obtained through in-depth interviews, direct observation, and documentation of company activities and stakeholder interactions. The findings show that the strategies used include advertising through social media platforms, local radio broadcasts, and podcasts; sales promotions such as free product samples and price discounts; direct marketing by participating in trade expos and exhibitions; and public relations initiatives through collaboration with key stakeholders such as Bank NTT, the Department of Trade, and local farming communities. The analysis reveals that customer brand awareness exists at varying levels—from unaware of the brand to top-of-mind recall. Nevertheless, weaknesses in digital content management and inconsistent social media engagement remain major obstacles to sustained communication efforts. This study concludes that a well-integrated and continuous marketing communication strategy is essential for strengthening brand positioning. The findings offer practical implications for local MSMEs seeking to build stronger market presence through adaptive and contextually appropriate communication strategies in the digital era.